Analisa Performa Internet Hotspot Area Menerapkan User Manager Menggunakan Router Mikrotik Di Lingkungan Perumahan - Wahju Tjahjo Saputro; Murhadi Murhadi; Dimas Yunianto Herbowo (INTEK : Jurnal Informatika dan Teknologi Informasi, 2021)
Communication without cable / wireless (wireless) has become a basic necessity or a new lifestyle of the information society. Wireless LAN, better known as Wi-Fi networks, is an alternative technology and is relatively easy to implement in a work environment. Installation of Wi-Fi network devices is more flexible because it does not require a cable connection between computers. An access point is a device commonly used in a wireless network (Hotspot area) where a user or users connect to the internet using air media through an access point device. In addition, this wireless-based network makes it easier for people to access the internet wherever they are. The implementation of this network installation consists of installing an RJ-45 connector on the UTP cable, configuring the router, configuring the Access Point, configuring the MikroTik HotSpot Server, and managing the user using the user manager feature. With the user manager-based HotSpot wireless network in a residential area, it will make it easier for residential residents to access the internet at a relatively low cost.